2005
DOI: 10.1210/me.2003-0379
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Placental Expression Analysis of the Human NRF3 Transcription Factor

Abstract: Members of the Maf protooncogene and cap'n' collar families of basic-leucine zipper transcription factors play important roles in development, differentiation, oncogenesis, and stress signaling. In this study, we performed an in vivo protein-protein interaction screen to search for novel partners of the small Maf proteins. Using full-length human MAFG protein as bait, we identified the human basic-leucine zipper protein NRF3 [NF-E2 (nuclear factor erythroid 2)-related factor 3] as an interaction partner. Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 56 publications
6
51
0
Order By: Relevance
“…Transcriptionally Activates ARE-driven Gene Expression-Electrophoretic mobility shift assays have demonstrated that Nrf3 can bind ARE sequences as a heterodimer with sMaf proteins (1,2,23). There are however conflicting reports about whether Nrf3 activates or suppresses ARE-driven gene expression.…”
Section: Nrf3mentioning
confidence: 99%
“…Transcriptionally Activates ARE-driven Gene Expression-Electrophoretic mobility shift assays have demonstrated that Nrf3 can bind ARE sequences as a heterodimer with sMaf proteins (1,2,23). There are however conflicting reports about whether Nrf3 activates or suppresses ARE-driven gene expression.…”
Section: Nrf3mentioning
confidence: 99%
“…16 Nrf3 heterodimerizes with MafK and MafG and this complex binds to the ␤-globin enhancer. 17,18 Nrf3 is able to represses antioxidant responsive elementmediated gene expression of antioxidant enzymes, such as the NAD(P)H:quinone oxidoreductase1 (NQO1) 19 and peroxiredoxin 6. 20 Recently we have shown that reactive oxygen species (ROS) are also involved in ESC differentiation toward SMCs.…”
mentioning
confidence: 99%
“…TFAP2C and IRF1 are not expressed in uterine microvascular endothelial cells in vivo (45)(46)(47). NFE2L3 has been suggested to play a potential role in placental gene expression and development (48). Interestingly, a previous study demonstrated that NFE2L3 is a negative regulator of NAD(P)H dehydrogenase NQO1 (49).…”
Section: Discussionmentioning
confidence: 99%